A 3-D numerical simulation-based heat production performance research for enhanced geothermal system with two horizontal wells and rectangular multiparallel fractures. (29th April 2022) - Li, Peng; Zheng, Jun; Dou, Bin; Tian, Hong; Liu, Hengwei; Xiao, Peng; Chen, Jinlong
Abstract: Parallel multifracture model with horizontal wells is an important structural form of enhanced geothermal system (EGS) to mine the hot dry rock, for its superiority in connecting injection well and production well. In this work, the numerical simulation study of the EGS heat production performance is carried out. Firstly, a 3-D large-scale model of two horizontal wells and multiparallel rough fractures is established, in which the fracture aperture are millimeter scale. Then, the flow and heat transfer process of water in fractured rock mass is simulated. Finally, sensitivity analysis of the EGS heat production performance to various operational and formation parameters is conducted, in which the well spacing, injection temperature, circulation flow rate, fracture aperture, fracture spacing and thermal conductivity of rock mass are considered. Results indicate that there are flow short circuit and blind angles in the velocity field, and the thermal short circuit exists in the temperature field of rock mass. EGS with four rough fractures can supply heat generation power of 9.11 MW–18.05 MW with an average value of 14 MW within 20 years, and the well spacing has the greatest influence on heat production performance of EGS while fracture aperture has least effect.